The significance of R&D investment and ICT usage in generating high income economy: an analysis on selected ASEAN countries / Chong Fen Nee ... [et al.] - Chong, Fen Nee; Suhaimi, Rosita; Lau, Evan, Poh Hock; Aba Ibrahim, Nurhani (Research Management Institute (RMI), 2013)
The main purpose of this study is to explore the impact of R&D investment on the proxies of income or wealth among ASEAN countries. Gross national income (GNI) per capital will be used as proxy of wealth in this study. This study is of significant because in order to cope with the globalization and transforming into knowledge based economy both the government and industries have beefed up efforts in R & D. Nevertheless, prior research only examined the significance of R&D investment at the firm rather than country level. Some believe that it enhances corporate growth while other found it generates higher income much later. In terms of methodology, multi-factor model will be employed as it is a better alternative comparing to the CAPM and APT in explaining variations in stock returns. Relevant data will be extracted from secondary resources. Furthermore, time series econometrics will be used to analyze and provide results to the objectives proposed in this study. Apart from providing additional information to the practitioners to facilitate better decision making in the future and enriching the existing literature to pave ways for more researchers to the academics, this study also intends to contribute useful input for future policy formulation.